Educação Ambiental em espaços não formais de ensino em Ibatiba-ES: contribuições para a assimilação de conteúdos conceituais, procedimentais e atitudinais por alunos do ensino médio. - Carvalho, Eder Junior Carlos de (2023)
Educational activities related to the subjects "Biology" and "environment" can foster the comprehensive development of students in terms of constructing knowledge about conceptual (knowing about), procedural (knowing how to do), and attitudinal (being) aspects of teaching and learning. The goal of this research was to analyze the contributions of an environmental education activity in a non-formal educational setting in the city of Ibatiba-ES to the comprehension of various types of content related to local socio-environmental issues. The research falls into the category of a qualitative study of the action research type and was conducted with 59 high school students in the 2nd year of a state school in Ibatiba-ES, along with a public agent for Technical Assistance and Rural Extension (ATER). In the first phase, we conducted an interview with the ATER agent to better understand the agricultural reality of the municipality and identify potential generative themes to be addressed in the didactic sequence. In the second phase, a pre-educational activity questionnaire was administered, and after the didactic sequence, a final questionnaire was used to assess the students’ learning. The questionnaire responses were analyzed using content analysis methodology with the assistance of the data management software ATLAS.ti. Through the interview with the ATER agent, it was identified that the municipality has great agricultural potential, with the use of pesticides in agricultural practices. Of the students participating in the research, 61% of them live in rural areas, and all engage in agricultural activities, such as pesticide application. It was found that 42.4% (25 students) of the participants had difficulty relating the objects of biological knowledge to everyday life and also lacked knowledge of conceptual, procedural, and attitudinal content. It was also observed that 35.6% of the students did not recognize actions related to environmental conservation and environmental education in their daily lives. Activities in non-formal educational settings are ideal for providing a contextualized approach, which facilitates the assimilation of conceptual, procedural, and attitudinal content related to Biology and the environment, strengthening the students’ understanding and fostering a commitment to socio-environmental issues.